Effect of Scaling and Root Planing with and without Diode Laser Application on Glycated Haemoglobin Levels in Type II Diabetic Patients with Chronic Periodontitis - Bhattarai, Anjali; Shrestha, Surendra Man; Pradhan, Ameena; Aryal, Shreya; Shrestha, Shilu (Journal of Nepalese Society of Periodontology and Oral Implantology, 2022)
Introduction: Periodontitis and diabetes have a combined systemic and local effect on tooth supporting structure and has been reported for decades. The gold standard treatment protocol would be scaling and root planing (SRP), which when combined with laser therapy has an additional benefit in the reduction of clinical parameters and glycated haemoglobin (HbA1c) levels. Objective: To evaluate the effectiveness of scaling and root planing with and without Diode laser application on glycated haemoglobin levels in type II diabetic patients with Chronic Periodontitis. Methods: Twenty eight type II diabetic patients with Chronic Periodontitis recruited by convenient sampling were divided into two groups in this pretest post-test study design. Group A received scaling and root planing (SRP) and Group B received SRP with diode laser (980 nm) application. The HbA1c levels were evaluated at three and six months; and clinical parameters were evaluated at one, three, and six months post-treatment. Data were analysed in SPSS v.20. Results: Mean values of HbA1c, probing depth (PD), clinical attachment level (CAL), plaque index (PI), and gingival index (GI) reduced significantly after treatment in both treatment groups with more reduction in laser group. However, on intergroup comparison HbA1c and CAL reduction were not significant. Conclusions: The findings of the current study showed significant improvements in HbA1c and clinical parameters as compared with baseline in patients treated with SRP and SRP + Diode Laser. Thus, use of diode laser showed no significant improvement statistically when used as an adjunct to scaling and root planing.